Vesicle-Like and 3D-Hexagonal Mesoporous SiO: Preparation and Laccase Adsorption Properties - H. Yang; L. Liu; B. S. Liang; H. M. Yuan; M. J. Tian; Y. X. Yang; Y. Huang (Adsorption Science & Technology)
3D hexagonal mesoporous silica (YPS) and vesicle-like mesoporous silica (YNS) were synthesized using H 3 PO 4 and HNO 3 as catalyst respectively, and environmental friendly sodium N-dodecyl glycine (YCS) as a green surfactant. The YPS and YNS samples were calcined at 550 °C, 700 °C and 850 °C. Their ordered meso-structures were characterized using infrared spectroscopy (IR), small-angle X-ray diffraction (SXRD), and high resolution transmission electron microscopy (HRTEM). Since YNS has special pore structure, it shows radiating channels with 20 nm shell around, while YPS shows random access channels. YNS not only has slightly larger pore size and IEP value than those of YPS but also possesses higher thermal stability. Precisely because of these factors, the pore of YNS-550 is characteristic of unique curvature, having stronger action with the lacease molecule than that between lacease molecule and YPS-550 with smaller pore curvature. So lacease adsorption isotherm of YPS-550 was V-type and that of YNS-550 was IV-type. The adsorption equation for lacease onto a mesoporous silica surface may be obtained as log[θ/(1 − θ)] = (log C + log K)/β.